Morphological, molecular and phylogenetic analyses of the spirurid nematode Stegophorus macronectes (Johnston & Mawson, 1942) - Vidal, Virginia; Ortiz, Juana; Diaz, Julia Inés; Zafrilla, Basilio; Bonete, Maria José; Ruíz de Ybañez, Maria Rocío; Palacios, Maria José; Benzal, Jesús; Valera, Francisco; de la Cruz, Carlos; Motas, Miguel; Bautista, Vanesa; et al. (Journal of Helminthology)
Stegophorus macronectes (Johnston & Mawson, 1942) is a gastrointestinal parasite found in Antarctic seabirds. The original description of the species, which was based only on females, is poor and fragmented with some unclear diagnostic characters. This study provides new morphometric and molecular data on this previously poorly described parasite. Nuclear rDNA sequences (18S, 5.8S, 28S and internal transcribed spacer (ITS) regions) were isolated from S. macronectes specimens collected from the chinstrap penguin Pygoscelis antarctica Forster on Deception Island, Antarctica. Using 18S rDNA sequences, phylogenetic analyses (maximum likelihood, maximum parsimony and Bayesian inference) of the order Spirurida were performed to determine the phylogenetic location of this species. Primer pairs of the ITS regions were designed for genus-level identification of specimens, regardless of their cycle, as an alternative to coprological methods. The utility of this molecular method for identification of morphologically altered specimens is also discussed. Fil: Vidal, Virginia. Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España. Museo Nacional de Ciencias Naturales. Departamento de Ecología Evolutiva; España Fil: Ortiz, Juana. Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico La Plata. Centro de Estudios Parasitológicos y de Vectores (i); Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Zafrilla, Basilio. Universidad de Alicante. Facultad de Ciencias; España Fil: Bonete, Maria José. Universidad de Alicante. Facultad de Ciencias; España Fil: Ruíz de Ybañez, Maria Rocío. Universidad de Murcia; España. Consejo Superior de Investigaciones Cientificas; España Fil: Palacios, Maria José. Consejo Superior de Investigaciones Cientificas. Estacion Experimental de Zonas Aridas; España ...